2007
DOI: 10.1507/endocrj.k07-047
|View full text |Cite
|
Sign up to set email alerts
|

Successful Intrauterine Therapy for Fetal Goitrous Hypothyroidism during Late Gestation

Abstract: Abstract. We experienced a case of fetal goitrous hypothyroidism in an infant delivered by a 33-year-old woman receiving 300 mg/day of propylthiouracil (PTU) for hyperthyroidism due to Graves' disease. A large fetal goiter (maximum diameter, 60 mm) was detected by magnetic resonance imaging (MRI) at 36 weeks of gestation. Initial fetal blood sampling revealed hypothyroidism with a serum thyroid-stimulating hormone (TSH) of 99 µIU/mL, free triiodothyronine (T 3 ) of 1.97 pg/mL, and free thyroxine (T 4 ) of 0.29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
(31 reference statements)
2
19
0
Order By: Relevance
“…39,44 In neither of these two cases did the goiters occur earlier in the pregnancy nor were they larger at the time of discovery than in other cases from group A or group B. Furthermore, cases of retarded bone development, 36,44,46 advanced bone ossifica tion 30 and congenital malformations 32 were reported across both groups (Table 2).…”
Section: Severe Complicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…39,44 In neither of these two cases did the goiters occur earlier in the pregnancy nor were they larger at the time of discovery than in other cases from group A or group B. Furthermore, cases of retarded bone development, 36,44,46 advanced bone ossifica tion 30 and congenital malformations 32 were reported across both groups (Table 2).…”
Section: Severe Complicationsmentioning
confidence: 90%
“…In total, we found 48 cases of fetal goitrous hypo thyroidism attributable to maternal ATD treatment reported in 20 case reports [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] and seven larger investigations [44][45][46][47][48][49][50] between 1980 and 2009. The cases were divided into two Figure 1 | Pathways of fetal goiter development in connection to maternal antithyroid drug treatment for Graves disease.…”
Section: Fetal Goitrous Hypothyroidismmentioning
confidence: 99%
“…It has been reported that the development of the human thyroid gland begins from GD 21 11 , and that the human thyroid gland is well developed by GD 70 in the first trimester and begins concentrating iodide and producing thyroid hormones at this time 11 . Compounds with a molecular weight greater than 1000 Da do not cross the placenta easily, whereas those of less than 600 Da, including thiamazole, freely cross the placenta 2–4,12–14 . In the present study, an excessive dosage of thiamazole affected the fetal thyroid glands through the placenta, inducing goiter in fetuses or neonates.…”
Section: Discussionmentioning
confidence: 99%
“…(Abuhamad et al ., 1995; Agrawal et al ., 2002; Hashimoto et al ., 2006; Miyata et al ., 2007; Hanono et al ., 2009; Ribault et al ., 2009). Potential causes of fetal goiter include primary dyshormonogenesis (Börgel et al ., 2005) and side effects of maternal antithyroid medication (Miyata et al ., 2007). In severe cases of this condition, the mass effect of a large fetal goiter can lead to polyhydramnios, head hyperextension, and airway obstruction at birth.…”
Section: Treatment For Fetal Thyroid Disordersmentioning
confidence: 99%